Macmillan English Dictionary for Advanced Learners - Rundell M. Michael (Oxford, Macmillan, 2007)
Find the meaning of words you read and hear menus take you straight to the right meaning — subject-specific vocabulary, World English and encyclopaedic entries, clear definitions using the most common words. Write and speak with confidence more information about the most frequent 7,500 words - the ideal vocabulary size for an advanced learner - which are printed in red and graded with stars, collocation boxes, vocabulary-building sections. Become a better learner by understanding how English works metaphor boxes, usage notes on style, grammar and varieties of English Language Awareness pages.